Exploring the Self/Group Initiated and On-the-Job Learning Activities of Low Income Women - Shauna Butterwick (Adult Education Research Conference, 2002)
This paper explores the breadth of learning undertaken by small group of low-income women who came together to explore various income generating ideas. Bringing into view these learning experiences disrupts some of the individualistic, sexist and classist assumptions about self-directed and on the-job learning dominating adult education and lifelong learning policy and programs.